Knowledge exchange and transformational leadership style for team improvement - WATTHANABUT, B. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThe principal objective of the current study was to explore the link between knowledge sharing, transformational leadership style, team performance, and mutual trust. In addition, the moderating role of mutual trust was also examined in the relationship of all other variables. Findings of the current study suggest team performance improves through the sharing of knowledge. The current study also viewed that team members share knowledge through coordination and that much of the knowledge shared is tacit. The study used PLS-SEM to analyses the data.RESUMENEl objetivo principal del presente estudio fue explorar el vínculo entre el intercambio de conocimientos, el estilo de liderazgo transformacional, el rendimiento del equipo y la confianza mutua. Además, el papel moderador de la confianza mutua también se examinó en la relación de todas las demás variables. Los resultados del estudio actual sugieren que el rendimiento del equipo mejora a través del intercambio de conocimientos. El estudio actual también observó que los miembros del equipo comparten conocimiento a través de la coordinación y que gran parte del conocimiento compartido es tácito. El estudio utilizó PLS-SEM para analizar los datos.